The Stakeholder's Perception of The National Education Standard Fulfilment Based on School Accreditation Grade (A Preliminary Study) - Marselus Ruben Payong; Hendrikus Midun; Oswaldus Bule (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to explore the opinions of basic education stakeholders regarding the fulfilment of national education standards in terms of school accreditation ratings. For this purpose, 307 stakeholders were involved (school principals, teachers, school committee members, and parents) from 43 elementary schools and 20 junior high schools in two sub-districts in Manggarai Regency, NTT. The method used was a cross-sectional survey. Data collection used a four-option (1-4) Likert scale questionnaire based on eight national education standards. The study results show that of the eight standards that stakeholders have assessed, two of them, namely the standards for teachers and standards for infrastructure, still need to be improved to the national standards. In addition, an analysis of the average differences using the Kruskal-Wallis Test analysis technique found differences in perceptions of achievement of the eight national education standards seen from the school's accreditation rating.